Delays in colonoscopy start time are associated with reductions in adenoma detection rates. Issue 8 (August 2020) - Laszkowska, Monika; Mahadev, Srihari; Hur, Chin; Green, Peter H.R.; Lebwohl, Benjamin
Abstract: Background: Prior investigations of the impact of case delays on adenoma detection rates have not found a significant association, though these studies included modest delays, with few cases delayed by more than one hour. Aims: The aim of this study was to measure the impact of prolonged case delays on the colonoscopy outcome measures of adenoma detection rate and withdrawal time. Methods: We performed a single center cohort study including patients aged ≥50 years undergoing screening colonoscopy during a 4.5 year period. Using multivariate regression, we measured the impact of delays on adenoma detection rate and withdrawal time, adjusting for age, gender, endoscopist, time of day of the procedure, and bowel preparation quality. Results: Of 7905 screening colonoscopies, 2503 (32%) were delayed by >1 h. On multivariable analysis, cases delayed 1–2 h were associated with a significant decrease in adenoma detection rate relative to cases delayed ≤1 h (OR 0.88, 95% CI 0.78–1.00, p = 0.049). Withdrawal time was not significantly associated with case delays. Conclusions: Prolonged case delays over 1 h are associated with reduced adenoma detection rates. Future research on factors underlying prolonged delays may help mitigate these barriers to care and improve quality outcomes.